Analysis of Cardiac Profile in Patients with Liver Cirrhosis: An Observational Study (Academia Journal of Medicine, 2018)
Background: Cirrhosis is defined as the histological development of regenerative nodules surrounded by fibrous bands in response to chronic  liver injury that leads to portal hypertension and end stage liver disease.Studies suggested that underlying cardiac dysfunction precedes the  development of Hepato-renal syndrome. hence; under the light of above mentioned data, we planned the present study to assess the cardiac  profile in patients with liver cirrhosis. Subjects and Methods: A total of 30 liver cirrhosis patients were included in the present study. Routine  haematological profile of all the patients was carried was assessed. Transthoracic 2 D echo with Doppler was done in all patients and  parameters (Left atrial enlargement, Left ventricular diastolic dysfunction) were assessed. Liver disease was staged according to Child-Pugh’s  score. All the results were compiled and analyzed by SPSS software. Results: Significant results were obtained while correlating the patients  with left atrial enlargement and severity of liver cirrhosis. Also, significant results were obtained while correlating the patients with diastolic  dysfunction and severity of liver cirrhosis. Conclusion: Cardiac parameters are directly correlated with the severity of the disease in liver  cirrhosis patients.
Keywords: Cardiac; Cirrhosis; Liver